(untitled) - Bot, Alexandra (Rome, 2005)
Soil organic matter - the product of on-site biological decomposition - affects the chemical and physical properties of the soil and its overall health. Its composition and breakdown rate affect: the soil structure and porosity; the water infiltration rate and moisture holding capacity of soils; the diversity and biological activity of soil organisms; and plant nutrient availability. This document concentrates on the organic matter dynamics of cropping soils and discusses the circumstances that deplete organic matter and their negative outcomes.
Keywords: Soil productivity,Năng suất đất